Planting character values through the implementation of MBKM in teaching campus programs - Sely Ayu Lestari; Innayatul Laili; Yuniar Mujiwati; M. Irwawan Siswantoro (Institute of Computer Science (IOCS), 2023)
This study uses qualitative research methods using respondents who come from university teaching participants. One of the learning activity programs in the Independent Learning Independent Campus (MBKM) is the Teaching Campus Program. This program has a target of primary and secondary schools. This program can be used as a means of instilling the values ??of the Indonesian nation's character to students in teaching campus placement schools. The instilled character values ??include 18 points. In addition, this program is considered quite effective as a forum for instilling student character values ??in schools assisted by students.